Null controllability of 1-d heat equation with switching controls - Taghiyev, Ali. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
In [1], Zuazua analyzed the problem of two switching controls for null controllability of the 1-d heat equation with Dirichlet's boundary conditions and obtained su cient conditions for null controls satisfying switching conditions. In this thesis, we consider the same problem with arbitrary number of switching controls and obtain su cient conditions for null controls satisfying switching conditions. Secondly, we consider the problem of switching controls for the null controllability of the 1-d heat equation with Robin's boundary condition and obtain su cient conditions for switching controls.
Keywords: Heat equation.